2012
DOI: 10.1039/c2sm25488c
|View full text |Cite
|
Sign up to set email alerts
|

Grain refinement and partitioning of impurities in the grain boundaries of a colloidal polycrystal

Abstract: We study the crystallization of a colloidal model system in presence of secondary nanoparticles acting as impurities. Using confocal microscopy, we show that the nanoparticles segregate in the grain boundaries of the colloidal polycrystal. We demonstrate that the texture of the polycrystal can be tuned by varying independently the nanoparticle volume fraction and the crystallization rate, and quantify our findings using standard models for the nucleation and growth of crystalline materials. Remarkably, we find… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
51
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 48 publications
8
51
0
Order By: Relevance
“…Previous investigation has focused on the effect of impurities that are either much larger [14,15,23] or much smaller [24] than their host colloids on crystallisation in three dimensions. These studies demonstrate that the texture of a colloidal polycrystal can be controlled through suitable choice of impurity size and concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigation has focused on the effect of impurities that are either much larger [14,15,23] or much smaller [24] than their host colloids on crystallisation in three dimensions. These studies demonstrate that the texture of a colloidal polycrystal can be controlled through suitable choice of impurity size and concentration.…”
Section: Introductionmentioning
confidence: 99%
“…A steady state is eventually reached at all probed length scales, preceded by an aging regime whose duration is unexpectedly length-scale dependent. and the rateṪ at which the temperature is increased to induce crystallization [29]. Here, we fixṪ = 0.02…”
mentioning
confidence: 99%
“…The sample microstructure can be tuned by varying the NP concentration and the rateṪ at which the temperature is increased to induce crystallization [29]. Here, we fixṪ = 0.02…”
mentioning
confidence: 99%
“…We now provide a model to account for the presence of a small amount of NPs of diameter σ P that are added to the copolymer suspension, at a volume fraction φ P . We have previously observed that upon solidification the NPs concentrate in the grain-boundaries and influence the microstructure of the polycrystals [33]. In the following, we neglect the effect of the diffusion of NPs on crystal growth, which could occur because of NPs partitioning, and thus assume that v G remains unchanged (Eq.…”
Section: B Nucleation Rate Growth Rate and The Effect Of Nanopartimentioning
confidence: 99%
“…We have shown using confocal microscopy [33] that the average grain size of Pluronics polycrystals can be tuned by changing the heating rate, a property well established for molecular and atomic systems, but hardly investigated in colloidal materials. In this paper, we deepen the experimental study of the role of the heating rate on Pluronics concentrated samples [34].…”
Section: Pacs Numbersmentioning
confidence: 99%